Pengaruh Pemberian Seduhan Serbuk Kayu Manis (Cinnamomun burmani Bi) Terhadap Penurunan Glukosa Darah Sewaktu - eli yusrita; Risky Riunika Tanjung (Jurnal Ilmu Kesehatan Abdurrab, 2023)
Cinnamon (Cinnamomun burmanii BI) can treat diabetes mellitus because it contains flavonoid compounds. The efficacy of flavonoids has been widely studied and scientifically proven to have a significant effect on lowering blood sugar levels. This study aims to determine the effect of steeping cinnamon powder (Cinnamomun Burmanii BI) on decreasing blood glucose levels while. The method used is pre and post sampling method. The results of research that have been conducted on the effect of steeping cinnamon powder (Cinnamomun burmani BI) on blood glucose reduction while at the PUSTU Cinta Damai Village, Tapung Hilir District, Kampar Regency, which was given for 14 days, the average blood glucose results before giving cinnamon powder steeping (Cinnamomum burmani BI) was 500.90 mg/dL and after infusion of cinnamon powder (Cinnamomun burmani BI) was 448.40 mg/dL. The average difference in blood glucose before and after the administration of cinnamon powder (Cinnamomun burmani BI) was 52,500 mg/dL. The results of the dependent paired t test (t test) obtained a P-value of 0.000 (P-value <0.05), this means that statistically there is an effect of steeping cinnamon powder (Cinnamomun burmani BI) on decreasing blood glucose while at PUSTU Cinta Damai Village, District Tapung Hilir, Kampar Regency.